Steel slag-based iron aluminate cement and preparation method thereof

Through physical grinding and acid treatment, the steel slag is activated, and the dispersion and cross-linking of ortho-dihydroxyphenol is used to solve the problem of steel slag powder agglomeration in cement, the good fluidity and mechanical properties of cement are achieved, and the use of cement is improved. life.

CN119390368AInactive Publication Date: 2025-02-07TECH SUPERVISION & RES CENT FOR BUILDING MATERIALS IND +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411609452.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, steel slag powder or fine particles of steel slag are prone to agglomeration in cement, resulting in reduced fluidity of the cement and unstable mechanical properties. The use of water reducing agents as dispersants may cause chemical reactions and reduce cement performance.

Method used

Steel slag is activated through dual activation of physical grinding and acid treatment, and the steel slag powder is dispersed by metal coordination and hydrogen bond adsorption of ortho-dihydroxyphenol, and the polydopamine structure formed by its self-crosslinking and polymerization is improved to improve the dispersion of steel slag powder and mix uniformity with cement.

Benefits of technology

It realizes effective dispersion of steel slag powder, improves the flowability and mechanical properties of cement, reduces the water absorption rate and the risk of expansion and cracking after calcination, and improves the service life of cement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses steel slag-based iron aluminate cement and a preparation method thereof, and belongs to the technical field of building cement materials. Comprising the following steps: crushing and mixing bauxite, limestone, gypsum and coarse steel slag, drying to constant weight, adding water, mixing, and performing wet grinding to obtain a test cake; drying the test cake to a constant weight, and calcining at a high temperature to obtain an aluminoferrite cement clinker; and mixing and finely grinding the steel slag powder dispersion, an aluminoferrite cement clinker, gypsum and fly ash to obtain the steel slag-based aluminoferrite cement. According to the invention, the activation treatment of the steel slag is realized through the dual activation effects of physical grinding and acid treatment, and then the dispersion of the steel slag powder is realized by virtue of the chemical adsorption and physical adsorption effects of metal coordination, hydrogen bond adsorption and the like of the o-dihydroxyphenol, so that the adverse effects of chemical reaction and the like possibly caused by the use of a water reducing agent are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building cement materials, and particularly relates to steel slag-based ferroaluminate cement and a preparation method thereof. Background Art

[0002] As the most important building material in today's society, cement is widely used in the construction industry due to its simple preparation process, low price, easy access to raw materials, and good mechanical properties. It has become an irreplaceable man-made building material. my country's cement production technology and output have always been at the forefront of the world, but due to the development of the cement industry and the needs of cement production technology, it consumes a lot of resources such as coal, limestone, etc., and releases harmful substances such as CO2 and solid dust, causing environmental pollution. Therefore, it is necessary to reduce the negative impact of cement production by adding cement admixtures, and to improve the performance of cement to a certain extent. Slag, fly ash, etc. have been widely used as cement admixtures in the field of cement concrete, and steel slag, as a solid waste, also has the potential to be used as a cement admixture. Steel slag is the main by-product of the steelmaking process and is a solid waste. my country is a major steel producer, and the emission of steel slag has exceeded 100 million tons. However, the utilization rate of steel slag in my country is far lower than that of developed countries abroad. A large amount of unused steel slag is piled up in the steel slag yard. The stacking and abandonment of steel slag not only occupies precious land resources, but also poses a serious threat to the safety of the atmosphere, soil, and groundwater. On the other hand, the chemical composition and mineral composition of steel slag determine that it has a certain degree of hydraulic hardness under alkaline conditions, so it can be used as a cement or concrete admixture, and the development of more resource utilization methods for steel slag is also of great significance. According to different steelmaking methods, steel slag includes converter steel slag, electric furnace steel slag and open-hearth steel slag. At present, the largest emission in my country is converter steel slag. Due to the gap in steelmaking process and technology, the chemical composition content of steel slag in different steel mills and even different batches is different, but the main components tend to be stable. The chemical composition of steel slag mainly includes CaO, SiO2, Al2O3, Fe2O3, FeO, MgO, MnO, P2O5 and elemental iron. The mineral composition of steel slag includes tricalcium silicate, dicalcium silicate, calcium aluminoferrite, metal oxide solid solution and a small amount of free oxide. Steel slag is generally not quenched after production, but slowly cooled in the air. During this process, the tricalcium silicate in the steel slag will decompose and the content will decrease. The metastable β-dicalcium silicate will also undergo lattice rearrangement and transform into a stable γ-dicalcium silicate. Therefore, compared with cement, the content of active minerals in steel slag is less and the activity is lower, making it difficult to be directly applied to the cement field.

[0003] In the prior art, steel slag is activated and modified so that it can be used in the preparation of mixing with cement. Modification technologies include physical excitation, chemical excitation and thermodynamic excitation. Among them, physical excitation is to increase the specific surface area of ​​steel slag by mechanical grinding, and then obtain steel slag powder to achieve the purpose of stimulating the activity of steel slag. Compared with other excitation methods, the physical excitation method of mechanical grinding has the advantages of low pollution, low energy consumption, simple processing and high economic benefits.

[0004] Patent CN107935419A discloses a modified steel slag cement, which comprises the following steps: crushing steel slag and sieving to obtain steel slag powder; stirring the steel slag powder with sulfuric acid, freezing and thawing cycles, filtering, and drying to obtain pretreated steel slag powder; ball-milling and stirring mixing potassium permanganate and the pretreated steel slag powder, and calcining at high temperature to obtain calcined steel slag powder; ball-milling and stirring mixing calcium carbonate and aluminum powder and the calcined steel slag powder, and burning to obtain modified steel slag powder; adding cement, modified steel slag powder, modified bagasse, silane coupling agent, and water into a mixer, stirring and mixing, and thus obtaining modified steel slag cement.

[0005] Patent CN107540250A discloses a pre-sorted steel slag phase-separated clinker cement production process, which selects pre-treated steel slag fine particles with a smaller particle size, then mixes them with raw materials and steel slag coarse particles and calcines them to obtain clinker, and finally mixes and grinds them with steel slag fine particles to obtain steel slag phase-separated clinker cement.

[0006] Patent CN109437637A discloses a steel slag cement expansive agent and silicate cement doped with the expansive agent. The invention mixes glycerol, strontium nitrate and water in a mass ratio of 1:1:50-80 to prepare an extraction solution, then soaks steel slag powder in the extraction solution, filters and removes the solution to obtain the steel slag cement expansive agent. The steel slag cement expansive agent is mixed with silicate cement to achieve an improvement in cement strength and other properties.

[0007] Although steel slag powder or steel slag fine particles can improve the mechanical properties of cement after being mixed with cement, due to the small particle size, large specific surface area and high surface energy of steel slag powder or steel slag fine particles, it is easy to cause powder or particles to agglomerate, reduce the fluidity of cement, and thus cause instability or even reduction of cement mechanical properties.

[0008] Patent CN114315183A discloses a method for in-situ growth of hydrated calcium silicate on the basis of steel slag to strengthen cement-based materials. In order to solve the agglomeration problem of steel slag powder, the invention adds polycarboxylic acid or naphthalene water reducer as a dispersant to improve the uniform dispersion of steel slag powder. Although the water reducer can effectively reduce the surface energy and thus improve the dispersibility of steel slag powder. However, due to the chemical structure characteristics of the water reducer, it sometimes reacts chemically with cement raw materials such as mineral admixtures, resulting in reduced cement performance, especially the amount used affects the porosity of cement (prone to increase the porosity), resulting in the steel slag powder losing the improvement of the porosity of the cement material, which is not conducive to improving the mechanical properties of cement.

[0009] Therefore, it is of great significance to study the method of achieving agglomeration modification of steel slag powder without using dispersants such as water reducers, and then to improve the mechanical properties of cement. Summary of the invention

[0010] In view of the deficiencies of the prior art, the present invention realizes the activation treatment of steel slag through the dual activation effects of physical grinding and acid treatment, and then disperses the steel slag powder by means of chemical adsorption and physical adsorption such as metal coordination and hydrogen bond adsorption of o-dihydroxyphenol, and then forms a polydopamine structure with strong cross-linking density and adhesion by means of the self-crosslinking polymerization of o-dihydroxyphenol, so as to realize the infiltration and filling of the pores on the acid-treated steel slag powder, and improve the mixing uniformity with ferroaluminate cement, thereby achieving low water absorption and good mechanical properties, and solving the technical problems raised in the background technology. Specifically, the technical scheme of the present invention includes the following contents:

[0011] One of the purposes of the present invention is to provide a method for preparing steel slag-based ferroaluminate cement, the preparation method comprising the following steps:

[0012] 15-25 parts by weight of bauxite, 40-45 parts by weight of limestone, 5-10 parts by weight of gypsum, and 10-25 parts by weight of crude steel slag are crushed, mixed, and dried to constant weight, and then 7-11 parts by weight of water are added, mixed, and wet-ground to form a test cake; the test cake is dried at 110° C. to 120° C. to constant weight, and then calcined at a high temperature of 1300° C. to 1400° C. for 30 min to 60 min to obtain ferroaluminate cement clinker;

[0013] The steel slag-based ferroaluminate cement is obtained by mixing and fine-grinding steel slag powder dispersion, ferroaluminate cement clinker, gypsum and fly ash.

[0014] Furthermore, the method for preparing the steel slag powder dispersion comprises the following steps:

[0015] The steel slag powder is treated with a weak acid solution for 4 h to 8 h to obtain an acid-treated steel slag powder;

[0016] The o-dihydroxyphenol compound is dissolved in Tris-hydrochloric acid buffer to form a substrate solution;

[0017] The acid-treated steel slag powder is dispersed in the substrate solution by ultrasonic method, and is immersed and cross-linked for 20h to 24h in a temperature environment of 20°C to 25°C to obtain the steel slag powder dispersion.

[0018] Furthermore, the steel slag powder is obtained by screening with a sieve of 50-100 meshes.

[0019] Furthermore, the mass concentration of the weak acid solution is 3% to 5%.

[0020] Furthermore, the weak acid used in the weak acid solution includes citric acid, malic acid or acetic acid.

[0021] Furthermore, the o-dihydroxyphenol compound includes dopamine hydrochloride or levodopa.

[0022] Furthermore, the pH of the Tris-hydrochloric acid buffer is 8.0-9.0.

[0023] Furthermore, the mass ratio of the o-dihydroxyphenol compound to Tris-hydrochloric acid buffer is 1:400-500.

[0024] Furthermore, the mass ratio of the acid-treated steel slag powder to the substrate solution is 1:2-3.

[0025] Furthermore, the conditions of the ultrasonic dispersion include an ultrasonic power of 200W to 300W and an ultrasonic time of 30min to 40min.

[0026] Furthermore, the weight ratio of the steel slag powder dispersion: ferroaluminate cement clinker: gypsum: fly ash is 30-36: 50-60: 3-5: 7-10.

[0027] The second object of the present invention is to provide steel slag-based ferroaluminate cement prepared by the method for preparing steel slag-based ferroaluminate cement.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The present invention adopts a physical powder method to grind steel slag to a certain particle size to obtain steel slag powder, realizes the primary activation of steel slag, and then uses weak acid to treat the surface of steel slag powder for secondary activation. The steel slag powder contains a large amount of metal oxides such as calcium oxide, aluminum oxide and iron oxide and a small amount of calcium silicate mixture. The weak acid treatment can promote the dissolution of these metal oxides and calcium silicate mixture to release metal ions and increase the porosity and roughness of the steel slag powder. Then, the acid-treated steel slag powder is immersed in a substrate solution through ultrasonic dispersion, and the substrate solution is infiltrated into the pore structure of the acid-treated steel slag powder. The substrate solution contains an o-dihydroxyphenol structure, which can form physical adsorption and chemical crosslinking with the surface of the acid-treated steel slag powder through active groups such as hydroxyl and amino groups with metal coordination and hydrogen bond adsorption, so as to realize the dispersion of the acid-treated steel slag powder. With the help of the self-polymerization of o-dihydroxyphenol in an alkaline environment to form a polydopamine structure with strong crosslinking density and strong adhesion, the synergistic coordination of ultrasonic dispersion, chemical crosslinking and hydrogen bond crosslinking not only improves the dispersibility of steel slag powder, which is conducive to uniform mixing with cement, but also reduces the adverse effects of the steel slag-based ferroaluminate cement obtained by mixing and grinding with ferroaluminate cement, which will increase the voids in the steel slag after acid treatment and easily absorb water, expand and crack. The strong crosslinking density and adhesion of the polydopamine structure formed by the self-crosslinking polymerization of o-dihydroxyphenol improve the mixing uniformity with ferroaluminate cement and reduce the adverse effects caused by the water absorption and expansion of ferroaluminate cement, so that the prepared steel slag-based ferroaluminate cement has good low water absorption and mechanical strength. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be clearly and completely described below through the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0031] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.

[0032] Preparation Example 1:

[0033] The preparation of steel slag powder dispersion specifically includes the following processes:

[0034] The steel slag was fed to a jaw crusher for crushing, and the obtained steel slag fragments were poured into a planetary ball mill and ground at a speed of 400 r / min for 30 min. The ground steel slag was screened with a 50-mesh square hole sieve to obtain steel slag powder.

[0035] Dissolve 300g of citric acid in 9.7kg of purified water and stir evenly to form a citric acid solution. Then take 2kg of steel slag powder and completely immerse it in the citric acid solution, stir and soak for 4 hours. After the soaking is completed, filter and collect the treated steel slag powder, and rinse the steel slag powder with a large amount of water until the pH value of the rinse waste liquid is neutral. Then place the steel slag powder in a drying oven and dry the water at a drying temperature of 70°C to obtain acid-treated steel slag powder.

[0036] Dissolve 10g of dopamine hydrochloride in 4kg of Tris-hydrochloric acid buffer with a pH of 8.0 to obtain a substrate solution. Take 1kg of acid-treated steel slag powder and add it to 2kg of substrate solution. Ultrasonic immersion treatment is performed at 200W of ultrasonic power for 20min. After the ultrasonic treatment, place it at room temperature for crosslinking for 20h. After the crosslinking is completed, filter out the steel slag powder, rinse it with Tris-hydrochloric acid buffer 3 times, then rinse it with purified water 3 times, and finally dry it in a drying oven at 60°C for 24h to obtain a steel slag powder dispersion.

[0037] Preparation Example 2:

[0038] The preparation of steel slag powder dispersion specifically includes the following processes:

[0039] The steel slag was fed to a jaw crusher for crushing, and the obtained steel slag fragments were poured into a planetary ball mill and ground at a speed of 400r / min for 30min. The ground steel slag was screened with a 50-mesh square hole sieve to obtain steel slag powder.

[0040] Dissolve 300g of citric acid in 9.7kg of purified water and stir evenly to form a citric acid solution. Then take 2kg of steel slag powder and completely immerse it in the citric acid solution, stir and soak for 4 hours. After the soaking is completed, filter and collect the treated steel slag powder, and rinse the steel slag powder with a large amount of water until the pH value of the rinse waste liquid is neutral. Then place the steel slag powder in a drying oven and dry the water at a drying temperature of 70°C to obtain acid-treated steel slag powder.

[0041] Dissolve 10g of dopamine hydrochloride in 4.2kg of Tris-hydrochloric acid buffer with a pH of 8.0 to obtain a substrate solution. Take 1kg of acid-treated steel slag powder and add it to 2.2kg of substrate solution, and ultrasonically immerse it at an ultrasonic power of 220W for 32 minutes. After the ultrasonic treatment, place it at room temperature for crosslinking for 20 hours. After the crosslinking is completed, filter out the steel slag powder, rinse it with Tris-hydrochloric acid buffer 3 times, then rinse it with purified water 3 times, and finally dry it in a drying oven at 60°C for 24 hours to obtain a steel slag powder dispersion.

[0042] Preparation Example 3:

[0043] The preparation of steel slag powder dispersion specifically includes the following processes:

[0044] The steel slag was fed to a jaw crusher for crushing, and the obtained steel slag fragments were poured into a planetary ball mill and ground at a speed of 400r / min for 30min. The ground steel slag was screened with a 50-mesh square hole sieve to obtain steel slag powder.

[0045] Dissolve 400g of malic acid in 9.6kg of purified water and stir evenly to form a malic acid solution. Then take 2kg of steel slag powder and completely immerse it in the malic acid solution, stir and soak for 6 hours. After the soaking is completed, filter and collect the treated steel slag powder, and rinse the steel slag powder with a large amount of water until the pH value of the rinse waste liquid is neutral. Then place the steel slag powder in a drying oven and dry the water at a drying temperature of 70°C to obtain acid-treated steel slag powder.

[0046] Dissolve 10g of dopamine hydrochloride in 4.4kg of Tris-hydrochloric acid buffer with a pH of 8.5 to obtain a substrate solution. Take 1kg of acid-treated steel slag powder and add it to 2.4kg of substrate solution, and ultrasonically immerse it at an ultrasonic power of 240W for 34 minutes. After the ultrasonic treatment, place it at room temperature for crosslinking for 22 hours. After the crosslinking is completed, filter out the steel slag powder, rinse it with Tris-hydrochloric acid buffer 3 times, then rinse it with purified water 3 times, and finally dry it in a drying oven at 65°C for 24 hours to obtain a steel slag powder dispersion.

[0047] Preparation Example 4:

[0048] The preparation of steel slag powder dispersion specifically includes the following processes:

[0049] The steel slag is fed to a jaw crusher for crushing, and the obtained steel slag fragments are poured into a planetary ball mill and ground at a speed of 400r / min for 30min. The ground steel slag is sieved through a 100-mesh square hole sieve to obtain steel slag powder.

[0050] Dissolve 400g of malic acid in 9.6kg of purified water and stir evenly to form a malic acid solution. Then take 2kg of steel slag powder and completely immerse it in the malic acid solution, stir and soak for 6 hours. After the soaking is completed, filter and collect the treated steel slag powder, and rinse the steel slag powder with a large amount of water until the pH value of the rinse waste liquid is neutral. Then place the steel slag powder in a drying oven and dry the water at a drying temperature of 70°C to obtain acid-treated steel slag powder.

[0051] Dissolve 10g of levodopa in 4.6kg of Tris-hydrochloric acid buffer with a pH of 8.5 to obtain a substrate solution. Take 1kg of acid-treated steel slag powder and add it to 2.6kg of substrate solution, and treat it by ultrasonic immersion at an ultrasonic power of 260W for 36min. After the ultrasonic treatment, place it at room temperature for crosslinking for 22h. After the crosslinking is completed, filter out the steel slag powder, rinse it with Tris-hydrochloric acid buffer 3 times, then rinse it with purified water 3 times, and finally put it in a drying oven at 65℃ for 24h to obtain a steel slag powder dispersion.

[0052] Preparation Example 5:

[0053] The preparation of steel slag powder dispersion specifically includes the following processes:

[0054] The steel slag is fed to a jaw crusher for crushing, and the obtained steel slag fragments are poured into a planetary ball mill and ground at a speed of 400r / min for 30min. The ground steel slag is sieved through a 100-mesh square hole sieve to obtain steel slag powder.

[0055] Dissolve 500g of acetic acid in 9.5kg of purified water and stir evenly to form an acetic acid solution. Then take 2kg of steel slag powder and completely immerse it in the acetic acid solution, stir and soak for 8h. After soaking, filter and collect the treated steel slag powder, rinse the steel slag powder with a large amount of water until the pH value of the rinse waste liquid is neutral. Then place the steel slag powder in a drying oven and dry the water at a drying temperature of 70℃ to obtain acid-treated steel slag powder.

[0056] Dissolve 10g of levodopa in 4.8kg of Tris-hydrochloric acid buffer with a pH of 9.0 to obtain a substrate solution. Take 1kg of acid-treated steel slag powder and add it to 2.8kg of substrate solution, and ultrasonically immerse it at an ultrasonic power of 280W for 38min. After the ultrasonic treatment, place it at room temperature for crosslinking for 24h. After the crosslinking is completed, filter out the steel slag powder, rinse it with Tris-hydrochloric acid buffer 3 times, then rinse it with purified water 3 times, and finally dry it in a drying oven at 70℃ for 24h to obtain a steel slag powder dispersion.

[0057] Preparation Example 6:

[0058] The preparation of steel slag powder dispersion specifically includes the following processes:

[0059] The steel slag is fed to a jaw crusher for crushing, and the obtained steel slag fragments are poured into a planetary ball mill and ground at a speed of 400r / min for 30min. The ground steel slag is sieved through a 100-mesh square hole sieve to obtain steel slag powder.

[0060] Dissolve 500g of acetic acid in 9.5kg of purified water and stir evenly to form an acetic acid solution. Then take 2kg of steel slag powder and completely immerse it in the acetic acid solution, stir and soak for 8h. After soaking, filter and collect the treated steel slag powder, rinse the steel slag powder with a large amount of water until the pH value of the rinse waste liquid is neutral. Then place the steel slag powder in a drying oven and dry the water at a drying temperature of 70℃ to obtain acid-treated steel slag powder.

[0061] Dissolve 10g of levodopa in 5kg of Tris-hydrochloric acid buffer with a pH of 9.0 to obtain a substrate solution. Take 1kg of acid-treated steel slag powder and add it to 3kg of substrate solution. Ultrasonic immersion treatment is performed at 300W of ultrasonic power for 40min. After the ultrasonic treatment, place it at room temperature for crosslinking for 24h. After the crosslinking is completed, filter out the steel slag powder, rinse it with Tris-hydrochloric acid buffer 3 times, then rinse it with purified water 3 times, and finally dry it in a drying oven at 70°C for 24h to obtain a steel slag powder dispersion.

[0062] Preparation Example 7:

[0063] The preparation of steel slag powder dispersion specifically includes the following processes:

[0064] The levodopa in Preparation Example 6 was replaced by catechol, and the other conditions were the same as those in Preparation Example 6.

[0065] Preparation Example 8:

[0066] The preparation of steel slag powder dispersion specifically includes the following processes:

[0067] The Tris-HCl buffer with a pH of 9.0 in Preparation Example 6 was replaced with a TE buffer with a pH of 8.0, and the other conditions remained the same as in Preparation Example 6.

[0068] Preparation Example 9:

[0069] The preparation of steel slag powder dispersion specifically includes the following processes:

[0070] The steel slag powder obtained by sieving with a mesh size of 100 in Preparation Example 6 was replaced with the steel slag powder obtained by sieving with a mesh size of 200, and acetic acid was replaced with hydrochloric acid. The other conditions remained the same as those in Preparation Example 6.

[0071] Preparation Example 10:

[0072] The preparation of steel slag powder dispersion specifically includes the following processes:

[0073] The ultrasonic dispersion in Preparation Example 6 was replaced by stirring at 200 r / min for 40 min, and the other conditions remained the same as in Preparation Example 6.

[0074] Embodiment 1:

[0075] A preparation method of steel slag-based ferroaluminate cement specifically includes the following steps:

[0076] 15 parts by weight of bauxite, 40 parts by weight of limestone, 5 parts by weight of gypsum and 10 parts by weight of crude steel slag were weighed and crushed with a crusher, then sieved and mixed to form a mixture, and the mixture was placed in a 105°C oven to dry until the weight no longer changed, then taken out and cooled to room temperature, 7 parts by weight of water was added to mix, and wet-milled in a ball mill at a speed of 30r / min for 30min, and then dried and pressed into a test cake. The test cake was placed in a 110°C oven to dry until the weight remained unchanged, and then placed in a high-temperature furnace, heated to 1300°C at a heating rate of 20°C / min and calcined for 30min to obtain ferroaluminate cement clinker.

[0077] 30 parts by weight of the steel slag powder dispersion obtained in Preparation Example 1, 50 parts by weight of ferroaluminate cement clinker, 3 parts by weight of gypsum and 7 parts by weight of fly ash were weighed and mixed and finely ground to obtain steel slag-based ferroaluminate cement.

[0078] Embodiment 2:

[0079] A preparation method of steel slag-based ferroaluminate cement specifically includes the following steps:

[0080] 18 parts by weight of bauxite, 41 parts by weight of limestone, 6 parts by weight of gypsum and 12 parts by weight of crude steel slag were weighed and crushed with a crusher, then sieved and mixed to form a mixture, and the mixture was placed in a 105°C oven to dry until the weight no longer changed, then taken out and cooled to room temperature, 8 parts by weight of water was added to mix, and wet-milled in a ball mill at a speed of 30r / min for 40min, and then dried and pressed into a test cake. The test cake was placed in a 110°C oven to dry until the weight remained unchanged, and then placed in a high-temperature furnace, heated to 1320°C at a heating rate of 20°C / min, and calcined for 30min to obtain ferroaluminate cement clinker.

[0081] 32 parts by weight of the steel slag powder dispersion obtained in Preparation Example 2, 52 parts by weight of ferroaluminate cement clinker, 3 parts by weight of gypsum and 7 parts by weight of fly ash were mixed and finely ground to obtain steel slag-based ferroaluminate cement.

[0082] Embodiment 3:

[0083] A preparation method of steel slag-based ferroaluminate cement specifically includes the following steps:

[0084] 20 parts by weight of bauxite, 42 parts by weight of limestone, 7 parts by weight of gypsum and 15 parts by weight of crude steel slag were weighed and crushed with a crusher, then sieved and mixed to form a mixture, and the mixture was placed in a 105°C oven to dry until the weight no longer changed, then taken out and cooled to room temperature, 8 parts by weight of water was added to mix, and wet-milled in a ball mill at a speed of 40r / min for 45min, and then dried and pressed into a test cake. The test cake was placed in a 110°C oven to dry until the weight remained unchanged, and then placed in a high-temperature furnace, heated to 1340°C at a heating rate of 20°C / min, and calcined for 40min to obtain ferroaluminate cement clinker.

[0085] 32 parts by weight of the steel slag powder dispersion obtained in Preparation Example 3, 54 parts by weight of ferroaluminate cement clinker, 4 parts by weight of gypsum and 8 parts by weight of fly ash were mixed and finely ground to obtain steel slag-based ferroaluminate cement.

[0086] Embodiment 4:

[0087] A preparation method of steel slag-based ferroaluminate cement specifically includes the following steps:

[0088] 22 parts by weight of bauxite, 43 parts by weight of limestone, 8 parts by weight of gypsum and 19 parts by weight of crude steel slag were weighed and crushed with a crusher, then sieved and mixed to form a mixture, and the mixture was placed in a 105°C oven to dry until the weight no longer changed, then taken out and cooled to room temperature, 10 parts by weight of water was added to mix, and wet-milled in a ball mill at a speed of 40r / min for 50min, and then dried and pressed into a test cake. The test cake was placed in a 110°C oven to dry until the weight remained unchanged, and then placed in a high-temperature furnace, heated to 1360°C at a heating rate of 20°C / min, and calcined for 50min to obtain ferroaluminate cement clinker.

[0089] 34 parts by weight of the steel slag powder dispersion obtained in Preparation Example 4, 56 parts by weight of ferroaluminate cement clinker, 4 parts by weight of gypsum and 8 parts by weight of fly ash were weighed and mixed and finely ground to obtain steel slag-based ferroaluminate cement.

[0090] Embodiment 5:

[0091] A preparation method of steel slag-based ferroaluminate cement specifically includes the following steps:

[0092] Weigh 24 parts by weight of bauxite, 44 parts by weight of limestone, 9 parts by weight of gypsum and 22 parts by weight of crude steel slag, crush them with a crusher, sieve and mix them to form a mixture, dry the mixture in a 105°C oven until the weight does not change, then take it out, cool it to room temperature, add 10 parts by weight of water, mix it, and wet grind it in a ball mill at a speed of 50r / min for 60min, then dry and press it into a test cake. The test cake is dried in a 110°C oven until the weight does not change, then placed in a high-temperature furnace, heated to 1380°C at a heating rate of 20°C / min, and calcined for 50min to obtain ferroaluminate cement clinker.

[0093] 36 parts by weight of the steel slag powder dispersion obtained in Preparation Example 5, 58 parts by weight of ferroaluminate cement clinker, 5 parts by weight of gypsum and 9 parts by weight of fly ash were mixed and finely ground to obtain steel slag-based ferroaluminate cement.

[0094] Embodiment 6;

[0095] A preparation method of steel slag-based ferroaluminate cement specifically includes the following steps:

[0096] 25 parts by weight of bauxite, 45 parts by weight of limestone, 10 parts by weight of gypsum and 25 parts by weight of crude steel slag are weighed and crushed with a crusher, then sieved and mixed to form a mixture, and the mixture is placed in a 105°C oven to dry until the weight does not change, then taken out and cooled to room temperature, 11 parts by weight of water are added, mixed, and wet-milled in a ball mill at a speed of 50r / min for 60min, and then dried and pressed into a test cake. The test cake is placed in a 110°C oven to dry until the weight does not change, and then placed in a high-temperature furnace, heated to 1400°C at a heating rate of 20°C / min and calcined for 60min to obtain ferroaluminate cement clinker.

[0097] 36 parts by weight of the steel slag powder dispersion obtained in Preparation Example 6, 60 parts by weight of ferroaluminate cement clinker, 5 parts by weight of gypsum and 9 parts by weight of fly ash were weighed and mixed and finely ground to obtain steel slag-based ferroaluminate cement.

[0098] Comparative Example 1:

[0099] A preparation method of steel slag-based ferroaluminate cement specifically includes the following steps:

[0100] The steel slag powder dispersion in Example 6 was replaced by the steel slag powder dispersion obtained in Preparation Example 7, and the other conditions remained the same as in Example 6.

[0101] Comparative Example 2:

[0102] A preparation method of steel slag-based ferroaluminate cement specifically includes the following steps:

[0103] The steel slag powder dispersion in Example 6 was replaced by the steel slag powder dispersion obtained in Preparation Example 8, and the other conditions remained the same as in Example 6.

[0104] Comparative Example 3:

[0105] A preparation method of steel slag-based ferroaluminate cement specifically includes the following steps:

[0106] The steel slag powder dispersion in Example 6 was replaced by the steel slag powder dispersion obtained in Preparation Example 9, and the other conditions remained the same as in Example 6.

[0107] Comparative Example 4:

[0108] A preparation method of steel slag-based ferroaluminate cement specifically includes the following steps:

[0109] The steel slag powder dispersion in Example 6 was replaced by the steel slag powder dispersion obtained in Preparation Example 10, and the other conditions remained the same as in Example 6.

[0110] According to "Rapid Hardening High-Iron Sulphoaluminate Cement" JC / T 933-2019, the steel slag-based ferroaluminate cement obtained in Examples 1 to 6 and Comparative Examples 1 to 4 was mixed with water and stirred, and then the compressive strength was measured on the 3rd day and the 28th day. The results are shown in Table 1 below.

[0111] Table 1

[0112]

[0113] The water absorption rate was determined according to the Test Procedure for Polymer Modified Cement Mortar DL / T 5126-2021. The results are shown in Table 2 below.

[0114] Table 2

[0115]

[0116] From Table 1 and Table 2 above, we can conclude that:

[0117] (1) The steel slag-based aluminoferrocement prepared in Examples 1 to 6 of the present invention realizes activation treatment of steel slag through the dual activation effects of physical grinding and acid treatment, and then disperses the steel slag powder by virtue of the chemical adsorption and physical adsorption effects such as metal coordination and hydrogen bond adsorption of o-dihydroxyphenol. Then, the o-dihydroxyphenol can self-crosslink and polymerize to form a polydopamine structure with strong crosslinking density and adhesion, thereby achieving infiltration and filling of pores on the acid-treated steel slag powder, and improving the mixing uniformity with aluminoferrocement. The cement has good compressive strength and low water absorption, and can increase the service life of the cement.

[0118] (2) It can be seen from Comparative Example 1 that although catechol has an o-dihydroxyphenol structure, due to the lack of amino groups, when it undergoes self-polymerization, the hydrogen bonding force and metal coordination are weaker than those of the amino-containing L-DOPA used in the present invention, resulting in a poor dispersion effect on acid-treated steel slag powder, and the strength of the self-polymerization is also weaker than that of the amino-containing L-DOPA used in the present invention, resulting in the final prepared steel slag-based ferroaluminate cement having a high water absorption rate and low mechanical strength.

[0119] (3) It can be seen from Comparative Example 2 that although TE buffer can disperse L-DOPA to form a substrate solution, the EDTA in the TE buffer has the function of chelating metal ions, so that the acid-treated steel slag powder is partially chelated in the TE buffer. The steel slag powder has a good effect on improving the strength of cement. Since the chelating effect of the buffer reduces the content of the steel slag powder, the mechanical properties of the steel slag-based ferroaluminate cement finally prepared are poor.

[0120] (4) From Comparative Example 3, it can be seen that although selecting steel slag powder with a smaller mesh size can improve the activity of steel slag, the steel slag powder with too small particle size may be over-acidified under the action of strong acid such as hydrochloric acid, which destroys the particle structure of the steel slag powder and inhibits the activation of the steel slag powder, resulting in the final prepared steel slag-based ferroaluminate cement having a higher water absorption rate and poorer mechanical properties.

[0121] (5) It can be seen from Comparative Example 4 that although the ortho-dihydroxyl group on the L-DOPA structure has the ability to coordinate and bond with the acid-treated steel slag powder, the acid-treated steel slag powder has a small particle size and still has a large specific surface area. It is difficult to disperse the acid-treated steel slag powder without ultrasonic pretreatment dispersion and only rely on the chemical cross-linking effect of metal coordination. As a result, the steel slag-based ferroaluminate cement finally prepared has a high water absorption rate and low mechanical properties.

[0122] The above-described embodiments provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected.

Claims

1. A method for preparing steel slag-based ferroaluminate cement, characterized in that: The preparation method comprises the following steps: Take 15-25 parts by weight of bauxite, 40-45 parts by weight of limestone, 5-10 parts by weight of gypsum, and 10-25 parts by weight of crude steel slag, crush and mix them, dry them to constant weight, then add 7-11 parts by weight of water, mix and wet grind to make a test cake; The test cake is dried at 110°C to 120°C to a constant weight, and then calcined at a high temperature of 1300°C to 1400°C for 30min to 60min to obtain ferroaluminate cement clinker; The steel slag-based ferroaluminate cement is obtained by mixing and fine-grinding steel slag powder dispersion, ferroaluminate cement clinker, gypsum and fly ash.

2. The method for preparing steel slag-based ferroaluminate cement according to claim 1, characterized in that: The method for preparing the steel slag powder dispersion comprises the following steps: The steel slag powder is treated with a weak acid solution for 4 h to 8 h to obtain an acid-treated steel slag powder; The o-dihydroxyphenol compound is dissolved in Tris-hydrochloric acid buffer to form a substrate solution; The acid-treated steel slag powder is dispersed in the substrate solution by ultrasonic method, and is immersed and cross-linked for 20h to 24h in a temperature environment of 20°C to 25°C to obtain the steel slag powder dispersion.

3. The method for preparing steel slag-based ferroaluminate cement according to claim 2, characterized in that: The mass concentration of the weak acid solution is 3% to 5%.

4. The method for preparing steel slag-based ferroaluminate cement according to claim 2, characterized in that: The o-dihydroxyphenol compound includes dopamine hydrochloride or levodopa.

5. The method for preparing steel slag-based ferroaluminate cement according to claim 2, characterized in that: The pH of the Tris-hydrochloric acid buffer is 8.0-9.

0.

6. The method for preparing steel slag-based ferroaluminate cement according to claim 2, characterized in that: The mass ratio of the o-dihydroxyphenol compound to the Tris-hydrochloric acid buffer solution is 1:400-500.

7. The method for preparing steel slag-based ferroaluminate cement according to claim 2, characterized in that: The mass ratio of the acid-treated steel slag powder to the substrate solution is 1:2-3.

8. The method for preparing steel slag-based ferroaluminate cement according to claim 1, characterized in that: The weight ratio of the steel slag powder dispersion: ferroaluminate cement clinker: gypsum: fly ash is 30-36:50-60:3-5:7-10.

9. A steel slag-based ferroaluminate cement prepared by the method for preparing a steel slag-based ferroaluminate cement according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Production technology of pre-sorted steel slag phase-splitting clinker cement

    CN107540250A

  • Modified steel slag cement

    CN107935419A

  • Steel slag cement expanding agent and Portland cement doped with expanding agent

    CN109437637A

  • Method for treating heavy metal ions by recycling modified manganese slag

    CN114735845A

  • Iron aluminate cement clinker, preparation method thereof and iron aluminate cement

    CN118529953A